2010
DOI: 10.1111/j.1467-8667.2010.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation of Vibration-Based Methods for Damage Assessment of Cable-Stayed Bridges

Abstract: This study investigated a number of different damage detection algorithms for structural health monitoring of a typical cable-stayed bridge. The Bayview Bridge, a cable-stayed bridge in Quincy, Illinois, was selected for the study. The focus was in comparing the viability of simplified techniques for practical applications. Accordingly, the numerical analysis involved development of a precise linear elastic finite element model (FEM) to simulate various structural health monitoring test scenarios with accelero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 47 publications
(58 reference statements)
0
60
0
Order By: Relevance
“…A comparative study of many of the aforementioned traditional, modal-based damage detection techniques was conducted by Talebinejad et al (2011). The study found that only highintensity damages were detectable through the application of these methods and that they were quite sensitive to noise contamination and that they identified numerous false damage events.…”
Section: Modal-based Damage Detection Techniquesmentioning
confidence: 99%
“…A comparative study of many of the aforementioned traditional, modal-based damage detection techniques was conducted by Talebinejad et al (2011). The study found that only highintensity damages were detectable through the application of these methods and that they were quite sensitive to noise contamination and that they identified numerous false damage events.…”
Section: Modal-based Damage Detection Techniquesmentioning
confidence: 99%
“…These methods are based on changes in the vibration characteristics on the structure, because vibration measurements are sensitive enough to detect damage, especially in the truss-type structures, where the vibration levels are high (Yan et al, 2012). The basic idea of vibration-based SHM is that modifications in structural characteristics affect the vibration response characteristics of structures (Talebinejad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many comparative studies have been conducted to assess the aforementioned modal parameters against each other, such as Talebinejad et al [71], who applied COMAC, DIM, MCM, and MFM to a FE model of a cable-stayed bridge subjected to varying degrees of excitation and noise. It was found that only large damage events were detected, as noise contamination reduced damage sensitivity.…”
Section: Summation Of Modal-based Damage Sensitive Featuresmentioning
confidence: 99%